Educational Solutions Amid a Moral Pandemic: Case Study at Islamic High School (MAN) 2 Kudus Boarding School - Yunita Prasetyani; Ashif Az-Zafi (Al-Hayat: Journal of Islamic Education, 2021)
This article aims to understand how the process of moral education that is applied during the Covid-19 pandemic through the boarding school system at MAN 2 Kudus. And the research method used is qualitative (field research) using several sources. The results obtained are that the implementation of the moral education process in MAN 2 Kudus is through habituation in every daily activity, secondly teaching material and the yellow book, the third is through giving advice. The sixth is through providing rewards and punishments.